Estimation of the viability of Brachiaria brizantha cv. MG-4 using the exudate pH test (Research, Society and Development, 2022)
Forages play a key role in obtaining products of high biological value in Brazil. In view of this, the genus Brachiaria (synonym Urochloa) stands out for its rusticity and adaptation to the natural climate and soil. However, the species has difficulty germinating both in the field and in the laboratory, due to dormancy, affecting the uniformity of the pasture. The tests commonly used to determine the viability of the seed presente some inconveniences, such as the prolonged period of execution. In view of this, the rapid tests stand out for the speed in process, for later disposal of batches of inferior quality. Thus, the objective of the research is to analyze the efficiency of the pH test of exudate-phenolphthalein for seeds of Brachiaria brizantha cv. MG-4. The work followed a completely randomized design (DIC), in a 2 x 5 factorial scheme, with two seed lots (scarified and intact) and five soaking times (0, 30, 60, 90 and 120 minutes), with four replications. The test showed that intact seeds had greater viability, with 98.40% of seeds capable of originating normal seedlings. The soaking times of seeds for the test showed that with the increase in the period leads to a loss of approximately 8.51% of viability. For the species under study, the time of 0 minutes (control) allowed the identification of a greater number of viable seeds in relation to the other times. The pH test of exudate-phenolphthalein is efficient in estimating the viability of intact seeds of Brachiaria brizantha cv. MG-4. Seed treatment with sulfuric acid impaired the seed viability test.